(3GdEJbGf aj Ydhe GdbQBfs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO Hf Ydi GdOjei GdCRgQi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMeO ddg GdPi CfRd Ydi YHOg GdcJGH hHYO aEf GdYde HMQ RaGQ dGjOQc bQGQ hbO bGd JYGdi eNGWHkG dNdbg heG ChJjJe ef GdYde GdEbdjdG s
(3BNQgG (B:s
(3hGJQc cdGe GdMGSOjf hHZjge gedG aHYO GdehJ jfbWY GdMSO fLR GdcJGH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HChdgG agQS HNW eZGjQ hUaMI GdYfhGf eMdGI HGdPgH fSNJ ai MjGI GdeUfas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs